Clinical evaluation of the urinary sediment after renal allotransplantation. Issue 2 (March 1970) - Papadimitriou, M.; Chisholm, G. D.; Kulatilake, A. E.; Shackman, R.
Abstract : The detection of lymphoid cells by routine examination of the urine after renal allotransplantation has proved to be a useful early indication of rejection. In a study of 36 rejection episodes, 20 (56%) were associated with a significant number of lymphocytes in the urine. The incidence was much higher when rejection occurred during the first month after operation (76%); lymphocytes were rarely found when rejection occurred after three months. The appearance of lymphocytes in the urine was of particular value for detecting rejection in patients with prolonged oliguria after transplantation.